Atlas of small animal CT and MRI - Wisner, Erik R.; Zwingenberger, Allison L. (Ames, Iowa : John Wiley & Sons, Inc., 2015)
Atlas of Small Animal CT & MRI is a highly illustrated diagnostic imaging guide to common clinical disorders of dogs and cats. Contains over 3,000 high quality CT, MRI and related diagnostic images Offers a unique approach emphasizing comparative imaging and pathologic correlation Focuses on important imaging features relevant to imaging diagnosis of disease in dogs and cats Written by internationally renowned experts in the field
Head & neck -- Brain -- Vertebral column & spinal cord -- Thorax -- Abdomen -- Musculoskeletal system.
Includes index.
Print version record and CIP data provided by publisher; resource not viewed.
Includes bibliographical references and index.
Keywords: Veterinary tomography; Veterinary diagnostic imaging; Magnetic resonance imaging; Diagnostic imaging; Magnetic resonance imaging; Veterinary diagnostic imaging; Veterinary tomography; Dog Diseases -- diagnosis; Cat Diseases -- diagnosis; Magnetic Resonance Imaging; Tomography, Emission-Computed.; Electronic books; Atlases